TIMP1 as a context-dependent biomarker linking cancer progression and cardiovascular disorders: a multi-level and bioinformatics study - Xie, Haomin; Zhou, Dianhua; Chen, Sicheng; Dai, Yining; Zhang, Ranran; Lin, Zongrong; Kong, Weiyi; Luo, Jianfang; Fu, Zhenyang (Frontiers in Immunology, 2026)
BackgroundTissue inhibitor of metalloproteinase 1 (TIMP1) plays diverse roles in extracellular matrix (ECM) remodeling, immune regulation, and tumor progression. However, its systemic patterns across cancers and cardiovascular disease remain incompletely understood.MethodsWe applied an integrative pipeline beginning with microarray analysis of tumor-bearing mouse hearts (GSE63032) to identify TIMP1 as a hub gene. Pan-cancer datasets from TCGA/GTEx and public portals were analyzed for expression, genomic alterations, epigenetic regulation, immune infiltration, prognosis, and drug sensitivity. Single-cell RNA-seq was used to define cell type–specific expression. As all large-scale analyses were performed using publicly available bioinformatics datasets, cell line experiments were used for targeted validation of TIMP1 expression and function. Findings were validated by immunohistochemistry, western blotting, and transwell assays in colorectal and gastric cancer models, with additional analysis performed in atherosclerosis cohort (GSE100927) and heart failing cohort (GSE5406) to explore cardiovascular relevance.ResultsTIMP1 was consistently upregulated across cancers, especially in colorectal and gastric tumors, where it correlated with adverse survival and high diagnostic accuracy. Genomic analyses revealed copy number alterations, while promoter hypomethylation aligned with increased expression in digestive cancers. Drug-response profiling indicated sensitivity to epigenetic inhibitors and resistance to MAPK-targeted agents. Single-cell analyses localized TIMP1 to myeloid cells in colorectal cancer and fibroblasts in gastric cancer, linking it to apoptosis, EMT, angiogenesis, and stromal–immune crosstalk. Beyond oncology, TIMP1 was elevated in atherosclerosis, aligning with immune- and lipid-related pathways, but reduced in heart failure, where it was linked to impaired mitochondrial metabolism.ConclusionThis multi-level and bioinformatics study identifies TIMP1 as a cross-disease regulator with context-dependent functions. TIMP1 serves as a potential prognostic and diagnostic biomarker in digestive cancers, a therapeutic stratification marker for epigenetic interventions, and a candidate mediator linking tumor biology with cardiovascular disorders such as atherosclerosis and heart failure.